Relationship between retinal sensitivity and disease activity in patients with psoriasis vulgaris (Clinics, 2015)
OBJECTIVES: Psoriasis is a hyperproliferative chronic inflammatory skin disease of unknown etiology and ocular structures and visual pathways can also be affected during the course of this disease. Subclinical optic neuritis has previously been observed in psoriatic patients in visual evoked potential studies. This trial was designed to evaluate retinal sensitivity in patients with psoriasis vulgaris. METHODS: A total of 40 eyes of 40 patients with chronic plaque-type psoriasis and 40 eyes of 40 age- and sex-matched control subjects were included in this study. The diagnosis of psoriasis was confirmed by skin biopsy. The severity was determined using the Psoriasis Area and Severity Index and the duration of the disease was recorded. After a full ophthalmological examination, including tests for color vision and pupil reactions, the visual field of each subject was assessed using both standard achromatic perimetry and short wavelength automated perimetry. RESULTS: The mean Psoriasis Area and Severity Index was 22.05±6.40′. There were no significant differences in the visual field parameters of subjects versus controls using either method. There were correlations between disease severity and the mean deviations in standard achromatic perimetry and short wavelength automated perimetry and between disease severity and the corrected pattern standard deviation and pattern standard deviation of short wavelength automated perimetry (r = -0.363, r = -0.399, r = 0.515 and r = 0.369, respectively). CONCLUSIONS: Retinal sensitivity appears to be affected by the severity of psoriasis vulgaris.